The Influence of Brand Ambassdor Agnez Mo on Lazada Consumer Purchase Intention in Bandung City - Okta Lista, Shandra; jamiat, Nuslih (Udayana Journal of Social Sciences and Humanities; Vol 5 No 2 (2021): UJoSSH, September 2021DO - 10.24843/UJoSSH.2021.v05.i02.p06, 2022)
This study was conducted to determine the effect of Agnez Mo as a Brand Ambassador on consumer buying interest at Lazada in the city of Bandung. This study aims to determine and analyze how Lazada consumers respond to the Brand Ambassador in Lazada, how the consumer's buying interest in Lazada, the magnitude of the influence of the Lazada Brand Ambassador on consumer buying interest in Lazada Bandung City. This research uses a quantitative method with a descriptive research type. The sampling technique was carried out using a non-probability sampling method with purposive sampling type, with a total of 100 respondents. The data analysis technique used is descriptive analysis and simple regression analysis. Based on the results of partial hypothesis testing (t-test) it was found that the Lazada Brand Ambassador variable had a significant negative effect on consumers' buying interest in Lazada Bandung City. This is evidenced by hypothesis testing showing that the Brand Ambassador variable (X) has a value of t-count (-4.167) < t-table (-1.984) and a significance level of 0.000 <0.05. Based on the coefficient of determination, it is found that the influence of the Brand Ambassador variable (X) on Purchase Interest (Y) is 15%. The conclusion of this study, the influence of the Lazada Brand Ambassador is in a bad category and has a significant negative effect on the buying interest of Lazada consumers in Bandung City.